Crime and justice in America : critical issues for the future - O'Brien, John T., 1924-; Marcus, Marvin (Pergamon policy studies on crime and justice., 1979)
Crime and Justice in America: Critical Issues for the Future details the importance of a unified justice system in the U.S. The title aims to tackle the measure that needs to be taken in order to develop a more unified system as to theory, profession, and separation of powers.